Luciferins Under Construction: A Review of Known Biosynthetic Pathways - Tsarkova, Aleksandra S. (Frontiers in Ecology and Evolution, 2021)
Bioluminescence, or the ability of a living organism to generate visible light, occurs as a result of biochemical reaction where enzyme, known as a luciferase, catalyzes the oxidation of a small-molecule substrate, known as luciferin. This advantageous trait has independently evolved dozens of times, with current estimates ranging from the most conservative 40, based on the biochemical diversity found across bioluminescence systems (Haddock et al., 2010) to 100, taking into account the physiological mechanisms involved in the behavioral control of light production across a wide range of taxa (Davis et al., 2016; Verdes and Gruber, 2017; Bessho-Uehara et al., 2020a; Lau and Oakley, 2021). Chemical structures of ten biochemically unrelated luciferins and several luciferase gene families have been described; however, a full biochemical pathway leading to light emission has been elucidated only for two: bacterial and fungal bioluminescence systems. Although the recent years have been marked by extraordinary discoveries and promising breakthroughs in understanding the molecular basis of multiple bioluminescence systems, the mechanisms of luciferin biosynthesis for many organisms remain almost entirely unknown. This paper seeks to provide a succinct overview of currently known luciferins’ biosynthetic pathways.